2005
DOI: 10.1002/jnr.20484
|View full text |Cite
|
Sign up to set email alerts
|

Investigations with cultured human microglia on pathogenic mechanisms of Alzheimer's disease and other neurodegenerative diseases

Abstract: Inflammation-mediated mechanisms for human neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) have evolved from being on the fringe of medical hypotheses to mainstream thinking. Pioneering immunopathology studies with human brain tissues identified microglia associated with neuropathologic hallmarks of these diseases. As activated macrophages were known to produce many potential toxic products, this gave rise to the hypothesis that activated microglia (brain resident macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 169 publications
(163 reference statements)
6
63
2
2
Order By: Relevance
“…It would thus seem that blood-derived microglia are beneficial to the diseased CNS. Although it has previously been suggested that microglial cells are unable to phagocytose b-amyloid in vivo, 76 our data demonstrate that newly differentiated microglial cells originating from the blood are able to remove bamyloid from extracellular environment, whereas resident microglia are ineffective at b-amyloid phagocytosis. 98 These data and the fact that b-amyloid is often found within lysosomes of bone marrowderived microglia suggest that newly infiltrated microglial cells may indeed be able to clear b-amyloid deposits by phagocytosis.…”
Section: Innate Immunity and Alzheimer's Diseasecontrasting
confidence: 84%
See 3 more Smart Citations
“…It would thus seem that blood-derived microglia are beneficial to the diseased CNS. Although it has previously been suggested that microglial cells are unable to phagocytose b-amyloid in vivo, 76 our data demonstrate that newly differentiated microglial cells originating from the blood are able to remove bamyloid from extracellular environment, whereas resident microglia are ineffective at b-amyloid phagocytosis. 98 These data and the fact that b-amyloid is often found within lysosomes of bone marrowderived microglia suggest that newly infiltrated microglial cells may indeed be able to clear b-amyloid deposits by phagocytosis.…”
Section: Innate Immunity and Alzheimer's Diseasecontrasting
confidence: 84%
“…Human brain samples of patients diagnosed with AD are usually obtained from very old subjects, a time where the disease is in its final stages. Our study may thus explain reports of human studies demonstrating a lack of b-amyloid phagocytosis by microglial cells, 76 since we have shown that b-amyloid is mostly phagocytosed by microglia originating from the blood and less often by resident microglial cells and that plaques in the later stages of their development contain many resident microglia, whereas there are fewer of their blood-derived counterparts. It is possible that resident microglia take part in b-amyloid deposition, [70][71][72] while bone marrow-derived cells serve to eliminate these deposits.…”
Section: Innate Immunity and Alzheimer's Diseasesupporting
confidence: 82%
See 2 more Smart Citations
“…Human elderly microglia were isolated and maintained in culture as previously described (Lue et al, 1996(Lue et al, , 2001Walker et al, 2005), using methods similar to those originally developed by Kim (1985). The cultured microglia expressed antigenic, morphologic, and other criteria of microglia, and were approximately 98% pure, confirming previous studies (Lue et al, 1996(Lue et al, , 2001Walker et al, 2005).…”
Section: Human Elderly Microglia Culturessupporting
confidence: 67%